Did Immigrants Perceive More Job Insecurity during the SARS-CoV-2 Pandemic? Evidence from German Panel Data - Marvin Bürmann; Jannes Jacobsen; Cornelia Kristen; Simon Kühne; Dorian Tsolak (Social Sciences, 2022)
Immigrants have been affected more than native-born ethnic majority populations by the negative economic consequences of the SARS-CoV-2 pandemic. This contribution examines whether they have also experienced higher levels of perceived job insecurity, reflected in a differential increase in financial concerns and the fear of job loss during the SARS-CoV-2 pandemic. This empirical study employs the SOEP-CoV survey, which assesses the socio-economic consequences of SARS-CoV-2. It is embedded in the ongoing German Socio-Economic Panel (SOEP). We present OLS models to compare perceptions of job insecurity across groups, capturing the situation before and during the pandemic. The analyses reveal that first-generation immigrants reported more financial worries, and they perceived a higher chance of job loss than second-generation immigrants and the native-born ethnic majority. This difference in economic concerns emerged only in the pandemic. Despite covering a wide range of conditions signaling objective risk of job loss, as well as individuals' means and resources for dealing with looming job loss, these disparities persisted in the empirical study. Considering group-membership-related feelings of acceptance and inclusion could provide a promising route for future inquiry that may allow the remaining gap in subjective job insecurity to be accounted for.
Keywords: 320; job insecurity; immigrants; labor market; migration; SARS-CoV-2; COVID-19; Germany